Complete chloroplast genomes of three Pleurozia species and comparative analyses with P. purpurea: codon usage bias and phylogeny - Bi, Sheng; Liu, Qin; Hao, Jie-Wei; Cai, Xiang-Zhe; Gao, De; Zhang, Li-Na (Frontiers in Plant Science, 2025)
The liverwort genus Pleurozia, a morphologically specialized bryophyte group, holds unique taxonomic and evolutionary significance. This study sequenced and assembled the chloroplast genomes of three Pleurozia species (P. acinosa, P. gigantea, and P. subinflata), with genome sizes of 118,233 bp, 118,423 bp, and 118,304 bp, respectively. All three genomes exhibit the typical quadripartite structure. Comparative genomics analyses, including the genome of P. purpurea, revealed high conservation in genome size, gene content, and inverted repeat (IR) boundaries. Coding regions were more conserved than noncoding and intronic regions, suggesting the potential of the latter as molecular markers. The IR regions also displayed significantly lower sequence divergence compared to the single-copy regions. Most protein-coding genes were subject to purifying selection, whereas ycf66 and ndhD showed signs of positive selection. Codon usage bias analyses across the four species identified a consistent preference for U- and A-ending codons, with a moderate bias primarily shaped by natural selection, in conjunction with mutation pressure. Phylogenetic analyses based on 35 liverwort chloroplast genomes strongly supported the monophyly of Pleurozia and confirmed Pleuroziales as an evolutionary intermediate between thalloid and leafy liverworts. These findings provide valuable genomic resources for improving our understanding of species delimitation, phylogenetic relationships, and evolutionary mechanisms in liverworts.